CRLF2 overexpression identifies an unfavourable subgroup of adult B-cell precursor acute lymphoblastic leukemia lacking recurrent genetic abnormalities. (February 2016) - Chiaretti, Sabina; Brugnoletti, Fulvia; Messina, Monica; Paoloni, Francesca; Fedullo, Anna Lucia; Piciocchi, Alfonso; Elia, Loredana; Vitale, Antonella; Mauro, Elisa; Ferrara, Felicetto; De Fabritiis, Paolo; Luppi, Mario; et al.
Highlights: 34% of adult B-lineage ALL without aberrations have high CRLF2 expression levels. In adult B-ALL, CRLF2 expression has prognostic significance. Also in adult B-ALL, CRLF2 is associated with JAK/STAT and IKZF1 lesions. Abstract: Background: A deregulated CRLF2 (d- CRLF2 ) expression was described in B-cell acute lymphoblastic leukemia without recurrent fusion genes (B-NEG ALL). While the role of d- CRLF2 in children has been extensively described, little is known about its role and impact in adult ALL. Methods: Expression levels of CRLF2 were evaluated by quantitative real-time PCR in 102 newly-diagnosed adult B-NEG ALL and correlated with the clinico-biological characteristics and outcome. Incidence and clinical impact of the P2RY8/CRLF2 transcript was also assessed. Results: High CRLF2 levels, as continuous variable, were significantly associated with hyperleucocytosis ( p  = 0.0002) and thrombocytopenia ( p  = 0.005); when a cut-point at ΔCt ≤ 8 was applied, 35 cases (34.3%), mostly males (80%), proved positive for CRLF2 expression. High CRLF2 levels, as continuous or categorical variable, were associated with a worse disease-free ( p  = 0.003 and p  = 0.015) and overall survival ( p  = 0.017 and 0.0038). Furthermore, when CRLF2 was analyzed as a categorical variable, a high statistical association was found with IKZF1 deletion and mutations in the JAK/STAT pathway ( p  = 0.001 and p  < 0.0001, respectively). Finally, the P2RY8/CRLF2 transcript, identified in 8/102 patients (7.8%), was associated with a poor outcome. Conclusions: In adult B-NEG ALL, high CRLF2 expression is associated with distinct clinico-biological features and an unfavourable prognosis in both univariate and multivariate analysis; similarly, P2RY8/CRLF2 positivity correlates with a poor outcome. The quantification of CRLF2 is an important prognostic marker in adult B-lineage ALL without known genetic lesions.